A longitudinal qualitative study to explore and optimize self-management in mild to end stage chronic kidney disease patients with limited health literacy: Perspectives of patients and health care professionals. Issue 1 (January 2022) - Boonstra, Marco D.; Reijneveld, Sijmen A.; Westerhuis, Ralf; Tullius, Janne M.; Vervoort, Johanna P.M.; Navis, Gerjan; de Winter, Andrea F.
Highlights: Innovative study, combining perspectives of patients with LHL and professionals. Due to limited information, patients are often unaware of kidney disease in primary care. Mental problems, resignation and failed attempts hinder to maintain self-management. Professionals lack competences to identify and communicate with LHL patients. Person-centered interventions targeting LHL patients and professionals, are needed. Abstract: Objectives: Limited health literacy (LHL) is associated with faster kidney deterioration. Health care professionals (HCPs) promote self-management to maintain kidney function, which is difficult for patients with LHL. Evidence lacks on perceived barriers and best strategies to optimize their self-management. Our study aims to explore experiences with and barriers for self-management from the perspectives of LHL patients and HCPs to identify strategies to optimize self-management. Methods: We performed a longitudinal qualitative study with semi-structured in-depth interviews and focus group discussions among CKD patients and LHL (n = 24) and HCPs (n = 37) from general practices and hospitals. Results: Four themes arose among patients: (1) CKD elusiveness, (2) suboptimal intake of knowledge (3) not taking a front-seat role, and (4) maintaining change. Among HCPs, three themes emerged: (1) not recognizing HL problems, (2) lacking effective strategies, and (3) health care barriers. Conclusion: We suggest three routes to optimize self-management: providing earlier information, applying person-centered strategies to maintain changes, and improving competencies of HCPs. Practice implications: HCPs need to explain CKD self-management better to prevent kidney deterioration. New interventions, based on behavioral approaches, are needed to optimize self-management. HCPs need training to improve recognition and support of LHL patients.